ANALISIS OPTIMALISASI MODAL KERJA PT UNILEVER INDONESIA TBK - Fera Maulina (Jurnal Ekonomi Integra, 2021)
ABSTRACT This study aims to determine working capital requirements and optimization of working capital at PT Unilever Indonesia Tbk. The form of research used is descriptive and uses secondary data obtained from PT Unilever Indonesia Tbk's 2015-2019 financial statements and other sources obtained from literature studies by studying books and journals that are related to the problem under study. The results showed that (1) PT Unilever Indonesia Tbk's need for working capital in 2016-2019 tends to increase. When compared with the available working capital (current assets), PT Unilever Indonesia is experiencing a lack of working capital to finance the company's operations. This lack of working capital will certainly cause PT Unilever Indonesia Tbk to experience liquidity problems, which is the inability to pay short-term obligations on time. Companies will seek credit as a source of funds in order to increase the fulfillment of current assets wealth needs in order to buy raw materials and even pay for employee salaries and other expenses. (2) PT Unilever Indonesia Tbk's optimal working capital in 2015-2018 tends to increase. The real working capital that is in the company is not optimal where the real working capital is not the same as the optimal working capital obtained. Real working capital less than optimal working capital will hamper or disrupt the smooth production or operational process because the company lacks funds. Even though the existing real working capital is not optimal, the amount obtained is not much lower than the optimal working capital.  Keywords: working capital management, workong capital requirements, optimization of working capital. ABSTRAK Penelitian ini bertujuan untuk mengetahui kebutuhan modal kerja dan optimalisasi modal kerja pada PT Unilever Indonesia Tbk. Bentuk penelitian yang digunakan adalah deskriptif dan menggunakan data sekunder yang diperoleh dari laporan keuangan PT Unilever Indonesia Tbk tahun 2015-2019 dan sumber lain yang diperoleh dari studi pustaka dengan mempelajari buku dan jurnal yang berkaitan dengan masalah yang diteliti. Hasil penelitian menunjukkan bahwa (1) Kebutuhan modal kerja PT Unilever Indonesia Tbk tahun 2016-2019 cenderung meningkat. Jika dibandingkan dengan modal kerja yang tersedia (aset lancar), PT Unilever Indonesia mengalami kekurangan modal kerja untuk membiayai operasional perusahaan. Kekurangan modal kerja ini tentunya akan menyebabkan PT Unilever Indonesia Tbk mengalami kesulitan likuiditas, yaitu ketidakmampuan membayar kewajiban jangka pendek tepat waktu. Perusahaan akan mencari kredit sebagai sumber dana guna meningkatkan pemenuhan kebutuhan kekayaan aset lancar guna membeli bahan baku bahkan membayar gaji karyawan dan biaya lainnya. (2) Modal kerja optimal PT Unilever Indonesia Tbk pada 2015-2018 cenderung meningkat. Modal kerja riil yang ada di perusahaan belum optimal dimana modal kerja riil tidak sama dengan modal kerja optimal yang diperoleh. Modal kerja riil yang kurang dari modal kerja optimal akan menghambat atau mengganggu kelancaran proses produksi atau operasional karena perusahaan kekurangan dana. Meskipun modal kerja riil yang ada belum optimal, namun jumlah yang diperoleh tidak jauh lebih rendah dari modal kerja optimal. Kata kunci: pengelolaan modal kerja, kebutuhan modal kerja, optimalisasi modal kerja